Students’ Stage Fright Symptoms in English Public Speaking Class - Meinawati, Euis; Purwaningrum, Prapti Wigati; Alawiyah, Sufi; Chodidjah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this research is to find out the symptoms of stage fright in students in English public speaking classes. The study approach uses a qualitative survey consisting of four open-ended questions. The data in this study were taken through direct observation of English public speaking classes, document reports on the progress of students learning public speaking from the teacher and interviews. The data analysis procedure was carried out in three stages, including 1) data reduction, which is the process of collecting data according to the focus of the research, 2) presenting data through the process of categorizing data, classifying and analyzing the process, and 3) drawing conclusions to find out the results. solving research problems. The results of the data analysis concluded that there were two general symptoms associated with student stage fright during public speaking class practice, namely physiological symptoms and cognitive symptoms. Thus, the teacher should be able to direct students to apply strategies to overcome speaking anxiety such as increasing preparation and practice. These findings have implications for teachers' understanding of the concept of the importance of understanding the character of students' anxiety in practicing English public speaking in class, so that teachers can choose learning methods or techniques that are appropriate to students' anxiety levels